Leksinis, gramatinis bei pragamatinis performatyvumo pobūdis - Zaikauskas, Egidijus (Kalbotyra, 2000)
Language presents a possibility of not only saying something about the world, but also of doing, creating something by uttering appropriate words. Such utterances are commonly called illocutionary or speech acts. Illocutionary acts express the illocutionary force of the speaker’s utterance. The clearest examples of illocutionary force are presented by “explicit performative utterances” (Austin, 1986, 67). The main part of such utterances consists of a performative verb used in an appropriate form. The basic notion defining a performative verb - performativity - has characteristics of three levels of language:- grammatical - the performative verb must be in the present tense because the illocutionary act is defined at the moment of utterance, etc.;- lexical- only verbs containing the semantic component of saying something (but not all of them) can make up (perform) illocutionary acts, etc.;- pragmatical - the performative utterance, unlike the constative utterance, can never be true or false, etc.So performativity is a complex phenomenon and it is of great importance for everyday and especially for juridical communication.